Maxillary molar intrusion with micro-implant anchorage (MIA) - Park Hyo-Sang; Jang Bong-Kyu; Kyung Hee-Moon (Sciendo, 2005)
Background: Intrusion of the maxillary molars is difficult to accomplish using traditional methods of anchorage.